OPTIMASI TRANSPOR Cu(II) DENGAN APDC SEBAGAI ZAT PEMBAWA MELALUI TEKNIK MEMBRAN CAIR FASA RUAH - Imelda, -; Kahar, Zaharasmi; Simarmata, Maria; Mustafa, Djufri (Universitas Andalas, 2012)
The transport of Cu(II) with Ammonium Pyrrolidine Dithiocarbamate(APDC) as carrier through bulk liquid membrane had been researched. The measurement was performed to source phase and feed phase by using Atomic Absorption Spectrophotometer toward Î»maks 324.7 nm. The result of the research showed the optimum condition to separate 20 ppm of Cu(II) was at pH 4 of source phase, concentration of APDC was 1 : 30, stirring time was 2 hours, and the stirring velocity was 300 rpm with the percentage of Cu(II) transport to feed phase was 97,06% and percentage of remains Cu(II) was 0%.